Latter-day saint library including the Encyclopedia of Mormonism (Infobases, 1998)
A CD-ROM containing a collection of reference works related to the Church of Jesus Christ of Latter-Day Saints. Works include the Holy Bible (KJV), The Book of Mormon, The Doctrine and Covenants, The Pearl of Great Price, The Encyclopedia of Mormonism, and teachings of Church leaders.